High-flux laser preparation method of graphene-loaded transition phosphide nanoparticles

Through the high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles, the problems of long reaction time, low yield and high operation difficulty in transition group phosphide catalyst synthesis in the prior art are solved, and rapid, efficient and universal catalyst synthesis is achieved, expanding the application scope and having industrial production prospects.

CN119797291APending Publication Date: 2025-04-11NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510109756.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art has problems such as long reaction time, low yield and high operation difficulty when synthesizing transition group phosphide catalysts, which are difficult to meet the needs of high efficiency and universality.

Method used

A high-throughput laser preparation method of graphene-loaded transition group phosphide nanoparticles was used to obtain a graphene substrate by laser etching of polyimide film, and a mixed solution of metal precursor salt and sodium hypophosphite was added dropwise, and then a secondary etching was used to synthesize different types of transition group metal phosphides.

Benefits of technology

The rapid synthesis of transition group phosphide catalysts has been achieved, the synthesis efficiency and universality have been improved, and more than 10 different types of phosphides can be synthesized simultaneously in a short period of time, expanding the scope of application, and having the prospect of industrial scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797291A_ABST
    Figure CN119797291A_ABST
Patent Text Reader

Abstract

The invention discloses a high-flux laser preparation method of graphene-loaded transition phosphide nano particles, and belongs to the technical field of nano materials. The high-flux laser preparation method comprises the following steps: scribing a polyimide film by using laser to obtain a graphene substrate, then dropwise adding a mixed solution of metal precursor salt and sodium hypophosphite with different components to the graphene substrate, carrying out vacuum drying, and then carrying out secondary scribing by using laser to obtain different types of transition metal phosphides, the graphene loaded transition phosphide nano particles are obtained. The preparation method is high in transition metal phosphide catalyst synthesis speed and high in universality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a high-throughput laser preparation method of graphene-loaded transition group phosphide nanoparticles. Background Art

[0002] Transition phosphides (TMPs) have attracted extensive attention in the fields of energy storage and catalysis due to their unique physical and chemical properties in catalysis, battery materials, and optoelectronic devices. In the field of catalysis, TMPs such as cobalt phosphide (CoP) and nickel phosphide (Ni 2 TMPs have been widely studied, especially in water electrolysis reactions, showing excellent catalytic activity and stability, becoming an important candidate material for efficient hydrogen production. In terms of energy storage, transition phosphides, as negative electrode materials for lithium-ion batteries and sodium-ion batteries, have high specific capacity and good cycle stability. For example, iron phosphide (FeP) can effectively improve the energy density and service life of the battery during the charging and discharging process. In addition, TMPs also perform well in optoelectronic applications. Some phosphides have good light absorption capabilities in the visible light range, which are suitable for photocatalysis and photodetectors, and contribute to the development of renewable energy technology. With the increasing demand for clean energy and efficient materials, the research hotspot of transition phosphides will continue to heat up, promoting their application in various high-tech fields.

[0003] Common methods for synthesizing transition phosphides include solid-phase reaction, hydrothermal / solvothermal, chemical vapor deposition, and electrochemical deposition. The typical solid-phase reaction method usually requires a long reaction time (>2h) to synthesize TMPs, which will lead to grain growth and affect the specific surface area and catalytic activity of TMPs. Although the hydrothermal / solvothermal method can synthesize a variety of TMPs with uniform morphology and controllable size, it also has the same problems as the solid-phase synthesis method, such as long time consumption. In addition, chemical vapor deposition and electrochemical deposition are usually used to synthesize TMPs films, but there are problems such as low yield and high difficulty in operation and control.

[0004] Therefore, it is extremely necessary to develop ultra-fast and highly universal synthesis methods for transition metal phosphide catalysts. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the object of the present invention is to provide a high-throughput laser preparation method for graphene-loaded transition metal phosphide nanoparticles, which can synthesize transition metal phosphide catalysts quickly and with high universality.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The invention provides a high-throughput laser preparation method of graphene-loaded transition metal phosphide nanoparticles. A polyimide film is scratched by laser to obtain a graphene substrate. A mixed solution of metal precursor salts and sodium hypophosphite with different components is then dripped onto the graphene substrate. After vacuum drying, the graphene substrate is scratched again by laser to obtain different types of transition metal phosphides, thereby obtaining graphene-loaded transition metal phosphide nanoparticles.

[0007] In one embodiment, the laser scribing rate when scribing the polyimide film is controlled to be 7×10 3 mm / s-7×10 5 mm / s, laser power is 3W-9W, and the scratching area is (2-10)mm×(2-10)mm.

[0008] In one embodiment, the metal precursor salt of different components is any one of nickel chloride hexahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate, cupric chloride dihydrate, hydrated indium nitrate, ammonium molybdate tetrahydrate, palladium chloride, platinum chloride hexahydrate, and sodium tungstate dihydrate.

[0009] In one embodiment, the molar ratio of the metal precursor salt solution to the sodium hypophosphite aqueous solution in the mixed solution of the metal precursor salts of different compositions and sodium hypophosphite is 1:(1-40).

[0010] In one embodiment, the concentration of the metal precursor salt solution is 0.01M-1M.

[0011] In one embodiment, the concentration of the sodium hypophosphite aqueous solution is 0.01M-4M.

[0012] In one embodiment, the amount of the mixed solution of the metal precursor salts of different compositions and sodium hypophosphite added is (80-10000) μL.

[0013] In one embodiment, the laser scribing rate of the secondary scribing is controlled to be 10 3 mm / s-10 5 mm / s, laser power is 3W-12W.

[0014] In one embodiment, the scribing area of ​​the secondary scribing is the same as the area of ​​the graphene substrate.

[0015] In one embodiment, the graphene-supported transition group phosphide nanoparticles are graphene-supported FeP nanoparticles, graphene-supported Fe 2 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported Ni 2 P nanoparticles, graphene-supported Cu3 P nanoparticles, graphene-supported MoP nanoparticles, graphene-supported Pd 5 P 2 Nanoparticles, Graphene-supported CoP nanoparticles, Graphene-supported InP nanoparticles, Graphene-supported OsP 2 Nanoparticles, graphene-supported PtP 2 Nanoparticles, graphene-supported Co 2 Any of P nanoparticles and graphene-supported WP nanoparticles.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a high-throughput laser preparation method for graphene-loaded transition phosphide nanoparticles. First, the laser preparation process used is simple and fast, and phosphides can be synthesized within a few microseconds by scratching a mixed solution of a metal precursor salt and sodium hypophosphite, which greatly improves the efficiency of phosphide synthesis; by dripping a mixed solution of a metal precursor salt and sodium hypophosphite with different components, the type and composition of the transition metal phosphide loaded on the graphene substrate can be accurately controlled. The laser secondary scratching process not only realizes the phosphating reaction of the metal precursor and sodium hypophosphite, but also can anchor the nanoparticles on the graphene substrate to a certain extent, thereby obtaining stable graphene-loaded transition phosphide nanoparticles with a single-phase structure. Secondly, the preparation method has high universality, and can simultaneously synthesize more than 10 different types of phosphides in a very short time, broadening its application range; finally, the laser synthesis method of phosphides has the advantages of high yield and high throughput, and has the prospect of realizing industrial-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 InP, Cu prepared in the embodiment of the present invention 3 P, Ni 2 P, OsP 2 and PtP 2 XRD spectrum of Figure 2 The Cu prepared in the embodiment of the present invention 3 SEM morphology photograph of P nanoparticles; Figure 3 The graphene loaded with InP(A), Cu 3 P(B),Ni 2 P(C), OsP 2 (D) and PtP 2 (E) TEM morphology and high-resolution images. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0019] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0020] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0021] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0022] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0023] The present invention provides a high-throughput laser preparation method of graphene-loaded transition group phosphide nanoparticles, comprising the following steps: First, a polyimide film is scratched with a laser to obtain a graphene substrate. Then, a mixed solution of metal precursor salts and sodium hypophosphite with different components is added to the graphene substrate. After vacuum drying, a second scratching with a laser is performed to obtain different types of transition metal phosphides.

[0024] As a material synthesis method with great potential, laser scribing has been applied to the synthesis of graphene, single element metals and multi-element alloys. It has the advantages of high precision, precise controllability, and ultra-fast heating and cooling rates (>105K / s). More importantly, laser scribing has high throughput characteristics, that is, it can carry out diversified experiments in a short time and quickly evaluate the synthesis effects under different conditions.

[0025] The specific steps of the above method are: 1) Use a laser engraving machine to scratch the commercial polyimide film to obtain the graphene substrate. The laser scratching rate is controlled at 7×10 3 mm / s-7×10 5 mm / s, laser power is 3W-9W, and the scratching area is (2-10)mm×(2-10)mm.

[0026] 2) Prepare aqueous solutions of various precursor salts with different concentrations (0.01M-1M) and sodium hypophosphite (NaH 2 PO 2 ) aqueous solution, the precursor salt is nickel chloride hexahydrate (NiCl 2 6H 2 O), ferric chloride hexahydrate (FeCl 3 6H 2 O), cobalt chloride hexahydrate (CoCl 2 6H 2 O), cupric chloride dihydrate (CuCl 2 2H 2 O), hydrated indium nitrate (In(NO 3 ) 2 xH 2 O), ammonium molybdate tetrahydrate ((NH 4 ) 2 MoO 4 4H 2 O), palladium chloride (PdCl 2 ), platinum chloride hexahydrate (H 2 PtCl 6 6H 2 O), sodium tungstate dihydrate (Na 2 WO 4 ·2H 2 O), osmium chloride hydrate (OsCl 3 xH 2 O), the precursor salt solution and sodium hypophosphite (NaH 2 PO 2 ) solutions were mixed in a certain molar ratio (1:1-1:40) and subjected to ultrasonic treatment for 5-10 min.

[0027] 3) The mixed solution was added dropwise to the graphene substrate in an amount of (80-10000) μL, and vacuum dried for 12 h to remove the water in the mixed solution. The graphene substrate was then scribed with a laser again to obtain graphene-supported transition group phosphide nanoparticles. The laser scribe rate was controlled to be 10 3 mm / s-10 5 mm / s, the laser power is 3W-12W, and the scratching area is the same as the graphene substrate area.

[0028] The prepared graphene-supported transition group phosphide nanoparticles are graphene-supported FeP nanoparticles, graphene-supported Fe 2 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported Ni 2 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported MoP nanoparticles, graphene-supported Pd 5 P 2 Nanoparticles, Graphene-supported CoP nanoparticles, Graphene-supported InP nanoparticles, Graphene-supported OsP 2 Nanoparticles, graphene-supported PtP 2 Nanoparticles, graphene-supported Co 2 Any of P nanoparticles and graphene-supported WP nanoparticles.

[0029] The following is a further detailed description of the present invention through specific examples, so as to better understand the essence and technical effects of the present invention. It should be clear that these embodiments are only for the purpose of illustrating the present invention and do not constitute any limitation to the present invention. After reading and understanding the technical content of the present invention, those skilled in the art can make various changes or modifications to the present invention without departing from the core idea of ​​the present invention, and these changes or modifications should also be regarded as a part of the present invention and fall within the scope of protection defined by the claims attached to this application.

[0030] In this example, all the instruments and equipment used are conventional in the art, and their operation and use follow conventional methods or the recommendations of the equipment manufacturers. Unless otherwise specified, all experiments were carried out under conventional conditions, and experimental conditions not explicitly stated can refer to the standard operating procedures in the relevant field.

[0031] Unless otherwise specified, all raw materials involved in the examples are products commonly sold on the market, and their specifications and quality meet the conventional standards in the field. In addition, in the specification of the present invention and subsequent examples, unless otherwise specified, "%" refers to weight percentage, "part" refers to weight part, and all proportional relationships are expressed based on weight ratio. Such an agreement is intended to make the description of the present invention clearer and more accurate, and to facilitate understanding and implementation.

[0032] Embodiment 1: The solution composition and concentration are as follows: 0.05MFeCl 3 6H 2 O solution and 2M NaH 2PO 2 Solution Preparation process of graphene-loaded FeP nanoparticle material: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​2×2 cm. 2 Then, 100 μL of 0.05 M FeCl was added dropwise. 3 Solution and 2MNaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 4.5 W and the laser scribing rate was 2.1 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported FeP nanoparticles.

[0033] Embodiment 2: The solution composition and concentration are as follows: 0.05MFeCl 3 6H 2 O and 0.5M NaH 2 PO 2 Solution Graphene loaded with Fe 2 Preparation process of P nanoparticle material: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​4×3 cm. 2 Then, 600 μL of 0.05 M FeCl was added dropwise. 3 solution and 0.05MNaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 3 W and the laser scribing rate was 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported Fe 2 Nanoparticles.

[0034] Embodiment 3: The solution composition and concentration are as follows: 0.8MCuCl 2 2H 2 O and 2.5M NaH 2 PO 2 Solution Graphene loaded Cu 3 Preparation process of P nanoparticle material: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​3×8 cm. 2 Then 1100 μL of 0.8 M CuCl was added dropwise. 2 2H 2O and 2.5M NaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 3 W and the laser scribing rate was 5.6 × 10 4 The graphene substrate was scratched again at a rate of mm / s to obtain the graphene-supported Cu 3 Nanoparticles.

[0035] Embodiment 4: The solution composition and concentration are as follows: 0.02MCoCl 2 6H 2 O and 1M NaH 2 PO 2 Solution Graphene loaded with Co 2 Preparation process of P nanoparticle material: First, a commercial polyimide film was laser scribed to obtain a graphene substrate with a scribed area of ​​10 × 10 cm 2 Then, 10000 μL of 0.02 M CoCl was added dropwise. 2 6H 2 O and 1M NaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 7 W and the laser scribing rate was 6.9 × 10 4 The graphene substrate was scratched again at a rate of mm / s to obtain the graphene-loaded Co 2 Nanoparticles.

[0036] Embodiment 5: The solution composition and concentration are as follows: 0.025MNiCl 2 6H 2 O and 3M NaH 2 PO 2 Solution Graphene loaded Ni 2 Preparation process of P nanoparticle material: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​10 × 5 cm. 2 Then, 5100 μL of 0.025 M NiCl was added dropwise. 2 6H 2 O and 3M NaH 2 PO 2 The solution was deposited on the graphene substrate and vacuum dried for 12 h. The laser power was 6 W and the laser scribing rate was 6.3 × 10 4The graphene substrate was scratched again at a rate of mm / s to obtain the graphene-supported Ni 2 Nanoparticles.

[0037] Embodiment 6: The solution composition and concentration are as follows: 0.65MIN(NO 3 ) 2 xH 2 O and 3M NaH 2 PO 2 Solution Preparation process of graphene-loaded InP nanoparticle materials: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​9×2cm. 2 Then 1800 μL of 0.65 M In(NO 3 ) 2 xH 2 O and 3M NaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 9 W and the laser scribing rate was 2.5 × 10 5 The graphene substrate is scratched again at a rate of mm / s to obtain graphene-loaded InP nanoparticles.

[0038] Embodiment 7: The solution composition and concentration are as follows: 0.01M(NH 4 ) 2 MoO 4 4H 2 O and 4M NaH 2 PO 2 Solution Preparation process of graphene-loaded MoP nanoparticle materials: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​5×5 cm. 2 Then, 6500 μL of 0.01 M (NH 4 ) 2 MoO 4 4H 2 O and 4M NaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 3 W and the laser scribing rate was 6.8 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-supported MoP nanoparticles.

[0039] Embodiment 8: The solution composition and concentration are as follows: 0.25MPdCl 2 2H 2 O and 2.5M NaH 2 PO 2 Solution Graphene loaded with Pd 5 P 2 Preparation process of nanoparticle materials: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​2×6 cm. 2 Then, 2400 μL of 0.8 M or 0.25 M PdCl was added dropwise. 2 2H 2 O and 2.5M NaH 2 PO 2 The solution was deposited on the graphene substrate and vacuum dried for 12 h. The laser power was 5 W and the laser scribing rate was 1.4 × 10 4 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded Pd 5 P 2 Nanoparticles.

[0040] Embodiment 9: The solution composition and concentration are as follows: 0.07MNa 2 WO 4 ·2H 2 O and 2.5M NaH 2 PO 2 Solution Preparation process of graphene-loaded WP nanoparticle material: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​4×10 cm 2 Then 8500 μL of Na 2 WO 4 ·2H 2 O and 2.5M NaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 3 W and the laser scribing rate was 10 5 The graphene substrate was scratched again at a rate of 1.5 mm / s to obtain graphene-loaded WP nanoparticles.

[0041] Embodiment 10: The solution composition and concentration are as follows: 0.05MCoCl 2 2H 2 O and 3M NaH 2 PO2 Solution Preparation process of graphene-loaded CoP nanoparticle materials: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​9×10 cm 2 Then, 9400 μL of 0.05 M CoCl was added dropwise. 2 2H 2 O and 3M NaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 8 W and the laser scribing rate was 9.5 × 10 4 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded CoP nanoparticles.

[0042] Embodiment 11: The solution composition and concentration are as follows: 0.05MCoCl 2 2H 2 O and 3M NaH 2 PO 2 Solution Preparation process of graphene-loaded CoP nanoparticle materials: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​9×10 cm 2 Then, 9400 μL of 0.05 M CoCl was added dropwise. 2 2H 2 O and 3M NaH 2 PO 2 The mixed solution was added to the graphene substrate and vacuum dried for 12 h. The laser power was 8 W and the laser scribing rate was 9.5 × 10 4 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded CoP nanoparticles.

[0043] Embodiment 12: The solution composition and concentration are as follows: 0.8MH 2 PtCl 6 6H 2 O and 2.5M NaH 2 PO 2 Solution Graphene-loaded PtP 2 Preparation process of nanoparticle materials: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​3×8 cm. 2 Then 1100 μL of 0.8 M H 2 PtCl6 6H 2 O and 2.5M NaH 2 PO 2 The solution was deposited on the graphene substrate and vacuum dried for 12 h. The laser power was 3 W and the laser scribing rate was 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded PtP 2 Nanoparticles.

[0044] Embodiment 13: The solution composition and concentration are as follows: 0.05MOsCl 3 xH 2 O and 2.5M NaH 2 PO 2 Solution Graphene-loaded OsP 2 Preparation process of nanoparticle materials: First, the graphene substrate was obtained by laser scribing a commercial polyimide film with a scribing area of ​​2×4 cm. 2 Then, 600 μL of 0.05 M OsCl was added dropwise. 3 xH 2 O and 2M NaH 2 PO 2 The solution was deposited on the graphene substrate and vacuum dried for 12 h. The laser power was 4.5 W and the laser scribing rate was 3.5 × 10 5 The graphene substrate was scratched again at a rate of mm / s to obtain graphene-loaded OsP 2 Nanoparticles.

[0045] Figure 1 InP, Cu prepared by this method 3 P, Ni 2 P, OsP 2 and PtP 2 From the XRD spectrum, we can see that except for the typical graphene peak (25.8°), the other peaks are pure phase phosphide peaks without other impurity phases. Figure 1 (A) corresponds to the standard InP phase ICSD (600858), Figure 1 (B) corresponds to the standard Ni 2 P-phase ICSD (27162), spectrum Figure 1 (C) corresponds to the standard Cu 3 P-phase ICSD (15056), spectrum Figure 1 (D) corresponds to the standard OsP 2 Phase ICSD (993), spectrum Figure 1(E) corresponds to the standard PtP 2 Phase ICSD(15026).

[0046] Figure 2 Cu 3 SEM morphology of P nanoparticles. From the figure, we can see that graphene has a porous structure and the phosphide nanoparticles are evenly loaded on the graphene.

[0047] Figure 3 For graphene loaded with InP(A), Cu 3 P(B),Ni 2 P(C), OsP 2 (D) and PtP 2 (E) TEM morphology and high-resolution images. The high-resolution TEM image further shows the typical structural information of single-phase phosphide. Figure 3 In (A), 0.338 nm corresponds to the (111) crystal plane of InP. Figure 3 (B) 0.215nm and 0.195nm correspond to Cu 3 The (211) and (113) crystal planes of P, Figure 3 In (C), 0.211nm and 0.169nm correspond to Ni 2 The (111) and (300) crystal planes of P, Figure 3 (D) 0.252nm and 0.261nm correspond to OsP 2 The (101) and (011) crystal planes of Figure 3 (E) 0.201nm corresponds to PtP 2 (220) crystal plane.

[0048] In summary, the present invention proposes a high-throughput laser preparation method for the rapid synthesis of graphene-supported transition phosphide nanoparticles. The method firstly has the characteristics of simple process and fast operation, and can complete the synthesis of phosphides in just a few microseconds, significantly improving the synthesis efficiency. Secondly, the preparation method is highly universal, and can simultaneously synthesize more than 10 different types of phosphides (such as graphene-supported FeP nanoparticles, graphene-supported Fe 2 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported Ni 2 P nanoparticles, graphene-supported Cu 3 P nanoparticles, graphene-supported MoP nanoparticles, graphene-supported Pd 5 P 2Nanoparticles, Graphene-supported CoP nanoparticles, Graphene-supported InP nanoparticles, Graphene-supported OsP 2 Nanoparticles, graphene-supported PtP 2 Nanoparticles, graphene-supported Co 2 P nanoparticles, graphene-loaded WP nanoparticles), which greatly expanded its application areas. Finally, due to the advantages of high yield and high throughput, the laser synthesis of phosphides has shown broad prospects for achieving industrial-scale production.

[0049] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A high-throughput laser preparation method for graphene-loaded transition group phosphide nanoparticles, characterized in that: A polyimide film is scratched with a laser to obtain a graphene substrate, and then a mixed solution of metal precursor salts and sodium hypophosphite of different compositions is added to the graphene substrate. After vacuum drying, the film is scratched again with a laser to obtain different types of transition metal phosphides, thereby obtaining graphene-loaded transition metal phosphide nanoparticles.

2. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 1, characterized in that: The laser scribing rate when scribing the polyimide film is controlled to be 7×10 3 mm / s-7×10 5 mm / s, laser power is 3W-9W, and the scratching area is (2-10)mm×(2-10)mm.

3. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 1, characterized in that: The metal precursor salts of different compositions are any one of nickel chloride hexahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate, cupric chloride dihydrate, hydrated indium nitrate, ammonium molybdate tetrahydrate, palladium chloride, platinum chloride hexahydrate, and sodium tungstate dihydrate.

4. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 1, characterized in that: The molar ratio of the metal precursor salt solution to the sodium hypophosphite aqueous solution in the mixed solution of the metal precursor salts of different components and sodium hypophosphite is 1:(1-40).

5. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 4, characterized in that: The concentration of the metal precursor salt solution is 0.01M-1M.

6. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 4, characterized in that: The concentration of the sodium hypophosphite aqueous solution is 0.01M-4M.

7. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 1, characterized in that: The amount of the mixed solution of the metal precursor salts of different compositions and sodium hypophosphite added is (80-10000) μL.

8. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 1, characterized in that: The laser scribing rate of the secondary scribing is controlled to be 10 3 mm / s-10 5 mm / s, laser power is 3W-12W.

9. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 1, characterized in that: The scribing area of ​​the secondary scribing is the same as the area of ​​the graphene substrate.

10. The high-throughput laser preparation method of graphene-supported transition group phosphide nanoparticles according to claim 1, characterized in that: The graphene-supported transition group phosphide nanoparticles are any one of graphene-supported FeP nanoparticles, graphene-supported Fe2P nanoparticles, graphene-supported Cu3P nanoparticles, graphene-supported Cu3P nanoparticles, graphene-supported Ni2P nanoparticles, graphene-supported Cu3P nanoparticles, graphene-supported MoP nanoparticles, graphene-supported Pd5P2 nanoparticles, graphene-supported CoP nanoparticles, graphene-supported InP nanoparticles, graphene-supported OsP2 nanoparticles, graphene-supported PtP2 nanoparticles, graphene-supported Co2P nanoparticles, and graphene-supported WP nanoparticles.